Effectiveness screening of SARS-CoV-2 (COVID-19) in the municipality of Andratx (Balearic Islands, Spain) - Margalida Monserrat-Mesquida; Margalida Monserrat-Mesquida; Margalida Monserrat-Mesquida; Maria Magdalena Quetglas-Llabrés; Maria Magdalena Quetglas-Llabrés; Maria Magdalena Quetglas-Llabrés; Cristina Bouzas; Cristina Bouzas; Cristina Bouzas; Silvia García; Silvia García; Silvia García; et al. (Frontiers in Public Health)
BackgroundThe coronavirus disease 2019 (COVID-19) pandemic was a global health emergency that significantly affected both the wellbeing of individuals and the global economy.ObjectiveThe aim of this study was to evaluate the degree of SARS-CoV-2 involvement, viral load, and immunological response in adults aged 18–65 who performed essential tasks in the municipality of Andratx (Balearic Islands, Spain) compared to those who did not. Additionally, the study examined these factors in children aged 2–18 years from both groups, if there were any.MaterialsBoth groups were monitored between July 2020 and February 2021, in which the degree of involvement, the viral load, and the immunological response to the SARS-CoV-2 were analyzed using questionnaires, polymerase chain reaction (PCR) tests, and ELISA serology tests.ResultsA positive case of RT-PCR test was found in screening the general population. The highest 2019-nCoV(N)-Ig antibody levels in plasma were measured from 1 to 17 February 2021, with the following percentage of positives: 6.8% of essential workers, 9.5% of essential workers’ sons, 7.3% of non-essential workers, and 2.2% of non-essential workers’ sons. However, an increase in levels of anti-SARS-CoV-2 (N) immunoglobulin G (IgG) and anti-SARS-CoV-2 (N) immunoglobulin M (IgM) were produced in session 3, from 9 to 25 November 2020, in both cases in non-essential workers, with a mean of 218.1 ng/mL of anti-SARS-CoV-2 (N) IgG and 31.3 ng/mL of anti-SARS-CoV-2 (N) IgM.ConclusionThe control measures taken to manage the COVID-19 pandemic in the municipality of Andratx, Mallorca, Spain, were effective.